Dermatological quality of life among leprosy patients residing at a rehabilitation center in North-Eastern India: A cross-sectional study - Sampriti Samanta; Alapan Bandyopadhyay; Sharmistha Bhattacherjee; Abhijit Mukherjee (Wolters Kluwer Medknow Publications, 2023)
Background: Leprosy has been affecting humans since ancient times. A chronic infectious disease, it affects skin, peripheral nervous system, and other tissues which lead to nerve damage, pain, and visible deformities. The characteristic skin lesions of leprosy can lead to significant social stigmatization and functional impairments which can affect the quality of life (QoL). Objective: The present study was conducted to assess the dermatological QoL among these leprosy patients. Materials and Methods: An observational cross-sectional study was conducted among 122 leprosy patients who were receiving treatments at a rehabilitation center in North-Eastern India in a 3-month time period. The dermatology QoL Index (DQLI) questionnaire was used to assess the QoL among these patients. Descriptive statistics and logistic regression analyses were used. Results: Among a total of 122 patients, leprosy had no effect on QoL in 4.9%, small effect in 11.5%, moderate effect in 37.7%, very large effect in 43.4%, and extremely large effect in 2.5% cases. Mean DQLI score was 10.5 ± 5.1. The most affected domain was leisure and social followed by symptoms and feelings. When adjusted for predictors, age and sex were found to have a significant association with QoL. Conclusions: Leprosy with dermatological manifestations had a very large effect on QoL. The impairment was more than other chronic skin diseases, such as chronic urticaria, vitiligo, and psoriasis. It is necessary that periodic assessment of QoL should be incorporated into the management of leprosy patients.